2012
DOI: 10.1038/onc.2012.507
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation stage of p53-Rb-deficient bone marrow mesenchymal stem cells imposes the phenotype of in vivo sarcoma development

Abstract: Increasing evidence suggests that mesenchymal stem/stromal cells (MSCs) carrying specific mutations are at the origin of some sarcomas. We have reported that the deficiency of p53 alone or in combination with Rb (Rb(-/-) p53(-/-)) in adipose-derived MSCs (ASCs) promotes leiomyosarcoma-like tumors in vivo. Here, we hypothesized that the source of MSCs and/or the cell differentiation stage could determine the phenotype of sarcoma development. To investigate whether there is a link between the source of MSCs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 43 publications
5
81
0
Order By: Relevance
“…5B). To get insight into the biologic functions affected by differentially expressed genes, we used Gorilla software (38)(39)(40) to perform GO analysis comparing KRAS-mutated versus KRAS nonmutated t(4;11) þ patients.…”
Section: Global Transcriptional Analysis Of T(4;11)mentioning
confidence: 99%
“…5B). To get insight into the biologic functions affected by differentially expressed genes, we used Gorilla software (38)(39)(40) to perform GO analysis comparing KRAS-mutated versus KRAS nonmutated t(4;11) þ patients.…”
Section: Global Transcriptional Analysis Of T(4;11)mentioning
confidence: 99%
“…[11][12][13] Mesenchymal stem cells (MSCs) that acquire mutations in oncogenes/TSGs such as p53 may function as tumor-initiating cells leading to de-novo sarcomagensis. [14][15][16][17] Furthermore, MSCs isolated from young mice, aged in culture acquired clinically relevant p53 mutations. 18 In all, these findings suggest a link between p53 inactivation in SCs and tumorigenesis.…”
mentioning
confidence: 99%
“…Of these, 196 (61%) were upregulated and 127 (39%) downregulated in lenalidomide-treated AML cells, establishing a lenaledomide-specific transcriptomic signature. To get insights into the biological functions affected by differentially expressed genes, we used the Gorilla software, 30,31 and found that many significant biological processes predicted to be activated in the lenalidomide-treated AML cells were associated with “migration/motility/mobilization/chemotaxis” (Figure 6A). In contrast, exposure of CB-CD34 + HSPCs to lenalidomide did not affect such biological functions (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Hierarchical clustering of genes was performed with the one minus correlation metric and the unweighted average distance. Only genes showing >1.5-fold change expression and p-value<0.05 were considered differentially expressed and were subjected to gene ontology (GO) term analysis using Gorilla 30,31 publicly available at http://cbl-gorilla.cs.technion.ac.il. Microarray data were deposited in the public Gene Expression Omnibus database, accession number GSE106748.…”
Section: Methodsmentioning
confidence: 99%